2021
DOI: 10.1128/mbio.03647-20
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in SARS-CoV-2 Patients: a Systematic Review and Meta-Analysis

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has rapidly spread across the globe at unprecedented speed and is showing no signs of slowing down. The outbreak of coronavirus disease 2019 (COVID-19) has led to significant health burden in infected patients especially in those with underlying comorbidities. The aim of this study was to evaluate the correlation between comorbidities and their role in the exacerbation of disease in COVID-19 patients leading to fatal outcomes. A systematic review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
175
3
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(246 citation statements)
references
References 98 publications
14
175
3
11
Order By: Relevance
“…Symptoms of COVID-19 can range from fever, cough, and fatigue to severe respiratory illness and death (25). Patient comorbidities increase the risk of hospitalization and severe COVID-19 (26,27). Using virus isolated from patients, the K18-hACE2 mouse model of SARS-CoV-2 infection has been shown to reproduce the features of severe COVID-19 (11).…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of COVID-19 can range from fever, cough, and fatigue to severe respiratory illness and death (25). Patient comorbidities increase the risk of hospitalization and severe COVID-19 (26,27). Using virus isolated from patients, the K18-hACE2 mouse model of SARS-CoV-2 infection has been shown to reproduce the features of severe COVID-19 (11).…”
Section: Discussionmentioning
confidence: 99%
“…Residents of counties with high SVI may experience greater prevalence of chronic health conditions that have been identified as comorbidities increasing the risk of mortality following SARS-CoV-2 infection, 21 including cancer, respiratory illness, cardiovascular illness, and diabetes. 22,23,24 These populations may also have poorer access to health care, especially the sophisticated medical care that is often required to mitigate severe and mortal COVID-19 outcomes. Furthermore, we observed an association of even greater magnitude between SVI Theme 3 (Minority Status & Language) and CFR, suggesting that communities of color and/or immigrant communities affected by COVID-19 may face greater risks of severe illness and mortality than white communities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in similar settings reported hypertension and diabetes as the commonly comorbid conditions among the hospitalized patients; for example, a nationwide analysis in China (Guan et al 2020) reported hypertension (19.9%), diabetes (8.2%). Additional to the single study, systematic reviews (Ng et al 2021; Sanyaolu et al 2020) and meta-analysis reported hypertension and diabetes as the common comorbid conditions among people infected by the virus.…”
Section: Discussionmentioning
confidence: 99%